2017
DOI: 10.1002/anie.201704020
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Regio‐ and Enantioselective [4+2] Annulation Reactions of Non‐activated Allenes by a Chiral Cationic Indium Complex

Abstract: Regio- and enantioselective [4+2] annulation between β,γ-unsaturated α-keto esters and non-activated allenes was achieved by using a chiral cationic indium(III)/phosphate catalyst. The reaction affords the corresponding C3-selective dihydropyrans in good yields and with high enantioselectivity (up to 99 % ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…ESI-MS experiment (cationic mode) gave two peaks m/z 1027.27 and 1728.45 corresponding to 5a ⋅Bi(OAc) 2 and ( 5a ) 2 ⋅Bi(OAc) 2 (for details, see Supplemental Information). A positive nonlinear effect between the catalyst's er value and product's er value was observed under optimal reaction conditions (Figure 3) (Liu et al., 2011, Wang et al., 2017), which indicates that more than one molecule of the chiral acid (S) - 5a is likely to be involved in the transition state of the enantio-differentiating step. The α-selectivity was observed with 1-methylallylboronic acid pinacol ester (Scheme 2, substrate scope part); thus, we speculated that the reaction should occur through a B-to-Bi transmetalation process (Chakrabarti et al., 2010).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…ESI-MS experiment (cationic mode) gave two peaks m/z 1027.27 and 1728.45 corresponding to 5a ⋅Bi(OAc) 2 and ( 5a ) 2 ⋅Bi(OAc) 2 (for details, see Supplemental Information). A positive nonlinear effect between the catalyst's er value and product's er value was observed under optimal reaction conditions (Figure 3) (Liu et al., 2011, Wang et al., 2017), which indicates that more than one molecule of the chiral acid (S) - 5a is likely to be involved in the transition state of the enantio-differentiating step. The α-selectivity was observed with 1-methylallylboronic acid pinacol ester (Scheme 2, substrate scope part); thus, we speculated that the reaction should occur through a B-to-Bi transmetalation process (Chakrabarti et al., 2010).…”
Section: Resultsmentioning
confidence: 97%
“…We suspected that the Brønsted acidity of chiral phosphoric acid is not strong enough to simultaneously activate ketimine 1a and allylboronate 2a . Inspired by Luo's asymmetric binary acid catalysis (Lv et al., 2011, Lv et al., 2013, Hashimoto et al., 2013, Hatano et al., 2015, Wang et al., 2017, Zhang et al., 2017a) and the bismuth catalyzed allylation of para -quinone with allylboronate 2a developed by our group (Zhang et al, 2017b), we proposed that this transformation was likely to be promoted by the BiX 3 -chiral phosphoric acid catalyst system and the use of chiral phosphoric acid could ensure the stereochemistry of this process. Gratifyingly, in the presence of (S) - 5a and Bi(OAc) 3 , the model reaction gave product 3a in quantitative yield with 87.9: 12.1 er (Table 1, entry 3).…”
Section: Resultsmentioning
confidence: 99%
“…An estimation based on UV absorption showed that approximately 76% of TP dissociated into trityl cations in the presence of InBr 3 . On the other hand, tritylium salts with a weakly coordinating metal-based monophosphate or bisphosphate anion could also be obtained when trityl bromide was treated with the corresponding metal phosphate, which can be prepared in situ following our previously described procedure (Scheme 2,c) [3738]. UV analysis indicated that the indium salt 1a or gallium salt 1b (0.05 mM) could induce ca.…”
Section: Resultsmentioning
confidence: 99%
“…Asymmetric hetero-Diels-Alder reactions have attracted considerable attention due to their ability to produce optically active heterocyclic molecules. [65][66][67][68][69][70][71] We conjectured that this nickel-catalyzed system was applicable to the inverse-electron-demand oxa-Diels-Alder ([4+2] annulation) of the α,β-unsaturated 2-acyl imidazoles once employing electron-rich alkenes as dienophiles. Indeed, under the identical conditions and in the presence of the same chiral nickel catalyst, the reaction of 2,3-dihydrofuran (2r) with the imidazole or benzimidazole substrates (1a, 1i-1s) gave the chiral bicyclic products (5a-5l) in 75-91% yields, with 11:1->20:1 dr and 87-Page 14 of 25 CCS Chemistry 97% ee (Scheme 5).…”
Section: Page 8 Of 25 Ccs Chemistrymentioning
confidence: 99%